2016
DOI: 10.1117/12.2232078
|View full text |Cite
|
Sign up to set email alerts
|

Radiation effects on the Gaia CCDs after 30 months at L2

Abstract: Since the launch of ESA's Gaia satellite in December 2013, the 106 large-format scientific CCDs onboard have been operating at L2. Due to a combination of the high-precision measurement requirements of the mission and the predicted proton environment at L2, the effect of non-ionizing radiation damage on the detectors was early identified pre-launch as potentially imposing a major limitation on the scientific value of the data. In this paper we compare pre-flight radiation-induced Charge Transfer Inefficiency (… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 20 publications
1
16
1
Order By: Relevance
“…No treatment of micro-meteoroid hits or micro-clanks was included (except for the exclusion of the data from short time intervals affected by large hits) leading to attitude modelling errors which in turn will limit the astrometric accuracy that can be attained (see Lindegren et al 2016, in particular appendix D). The treatment of CTI effects was not included in Gaia DR1, which is justified given the present low levels of radiation damage to the Gaia CCDs (Crowley et al 2016a). We stress that the above description of the data processing for Gaia DR1 is mainly illustrative and not intended as a complete description of all the simplifications that were introduced to enable a timely first Gaia data release.…”
Section: Data Processing Simplifications For Gaia Dr1mentioning
confidence: 99%
“…No treatment of micro-meteoroid hits or micro-clanks was included (except for the exclusion of the data from short time intervals affected by large hits) leading to attitude modelling errors which in turn will limit the astrometric accuracy that can be attained (see Lindegren et al 2016, in particular appendix D). The treatment of CTI effects was not included in Gaia DR1, which is justified given the present low levels of radiation damage to the Gaia CCDs (Crowley et al 2016a). We stress that the above description of the data processing for Gaia DR1 is mainly illustrative and not intended as a complete description of all the simplifications that were introduced to enable a timely first Gaia data release.…”
Section: Data Processing Simplifications For Gaia Dr1mentioning
confidence: 99%
“…3. The radiation damage to the CCD detectors is measured through first-pixel response in the along-scan profiles of lines of charge injection and through onboard counters registering the number of rejected detections in the sky mapper; this radiation damage is generally as expected, essentially showing a slow yet persistent degradation, caused by the omnipresent flux of high-energy Galactic cosmic rays (a handful of particles cm −2 s −1 ), combined with a handful of discontinuities corresponding to solar activity and associated proton events (Kohley et al 2014;Crowley et al 2016a). The data also show a clear sign of the well-known anti-correlation between cosmic-ray fluxes and solar activity (e.g.…”
Section: Orbit and Environmentmentioning
confidence: 99%
“…In fact, a study (Hopkinson et al 2010) that compared the effects of trapping between warm (room temperature) and cold (133 K) proton irradiated sections of a Gaia CCD found that the trap densities were generally around a factor of two higher for the cold-irradiated section than for the warm-irradiated section. A detailed analysis of the L2 radiation environment seen by Gaia can be found in Crowley et al (2016).…”
Section: Comparison To Pre-flight Expectationsmentioning
confidence: 99%